2003
DOI: 10.1046/j.1365-2788.2003.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an intervention system for parents of children with intellectual disability and challenging behaviour

Abstract: Finally, there were minimal differences among the three modes of delivery on the measures used, although families who used the self-directed mode were less likely to complete the materials. Implications of these results for service delivery are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
94
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 24 publications
9
94
1
6
Order By: Relevance
“…This study supports and extends the findings of previous research (Harrold et al, 1992;Hudson et al, 2003;Huynen et al, 1996;Roberts et al, 2006;Sanders & Plant, 1989) which demonstrates the efficacy of behavioral parent training with parents of children with developmental disabilities. These studies have generally reported reductions in child problem behavior and improvements in positive parent behavior following parent programs involving contingency management training, planned activities training, compliance training, or a combination of these programs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study supports and extends the findings of previous research (Harrold et al, 1992;Hudson et al, 2003;Huynen et al, 1996;Roberts et al, 2006;Sanders & Plant, 1989) which demonstrates the efficacy of behavioral parent training with parents of children with developmental disabilities. These studies have generally reported reductions in child problem behavior and improvements in positive parent behavior following parent programs involving contingency management training, planned activities training, compliance training, or a combination of these programs.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, Hudson et al (2003) investigated the effectiveness of a behavioral parent training program which focused on enhancing parent-child interactions, replacing problem behavior with appropriate behavior, planning for appropriate behavior, and teaching children new skills. Following training parents reported improved child behavior, that they were more effective in managing their child's behavior, and were less stressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The remainder of this chapter is organized into three sections: (a) trends and issues, (b) future research and limitations, and (c) conclusion. Although interventions for parents of children with IDD have received some attention in the parent education literature [45][46][47][48][49][50][51][52][53][54][55][56], it appears that the majority of recent parent education interventions have included parents of children with ASD rather than children with an intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of parent training programmes have been developed to address such behavioural problems in children with developmental disabilities (Baker & Abbott Feinfield, in press;GavidiaPayne & Hudson, 2002;Hudson, 2000;Lutzker & Steed, 1998), including group-based behavioural parent training programmes (e.g., Brightman, Baker, Clark & Ambrose, 1982;Chadwick, Morncilovic, Rossiter & Stumbles, 2001;Heifetz, 1977;Hudson, 1985;Hudson et al, 2003;Jocelyn, Casiro, Beattie, Dow & Kneisz, 1998;Kashima, Baker & Landen, 1988;Prieto-Bayard & Baker, 1986;Tavormina, 1975). In parallel with these developments in the disability field, videomodelling assisted training packages for use in group-based settings for parents of children with conduct problems (but without developmental disabilities) have been developed and the efficacy of these programmes is well established (e.g., Behan & Carr, 2000;Webster-Stratton & Reid, 2003).…”
mentioning
confidence: 99%